2003
DOI: 10.1254/jphs.92.50
|View full text |Cite
|
Sign up to set email alerts
|

Matricaria chamomilla Extract Inhibits Both Development of Morphine Dependence and Expression of Abstinence Syndrome in Rats

Abstract: The effect of Matricaria chamomilla (M. chamomilla) on the development of morphine dependence and expression of abstinence was investigated in rats. The frequencies of withdrawal behavioral signs (paw tremor, rearing, teeth chattering, body shakes, ptosis, diarrhea, and urination) and weight loss induced by naloxone challenge were demonstrated in morphine-dependent rats receiving M. chamomilla extract or saline. The withdrawal behavioral manifestations and weight loss were inhibited significantly by chronic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…Administration of W. somnifera (L.) Dunal (100 mg/kg) for 9 days attenuated the development of tolerance to the analgesic effect of morphine (10 mg/kg). W. somnifera (100 mg/kg) also suppressed morphine-withdrawal jumps, a sign of the development of dependence to opiate as assessed by naloxone (2 mg/kg) precipitation withdrawal on day 10 of testing [5][6]. The present experiments were undertaken to study the protective effect of W. coagulans root extract on the development of dependence to morphine in mice.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Administration of W. somnifera (L.) Dunal (100 mg/kg) for 9 days attenuated the development of tolerance to the analgesic effect of morphine (10 mg/kg). W. somnifera (100 mg/kg) also suppressed morphine-withdrawal jumps, a sign of the development of dependence to opiate as assessed by naloxone (2 mg/kg) precipitation withdrawal on day 10 of testing [5][6]. The present experiments were undertaken to study the protective effect of W. coagulans root extract on the development of dependence to morphine in mice.…”
Section: Introductionmentioning
confidence: 93%
“…0.5 h after the final dose of morphine. Withdrawal syndrome was assessed by counting the number of jumping episodes for 60 min after naloxone injection [1,[6][7][8].…”
Section: Drug and Fractions Treatmentmentioning
confidence: 99%
“…So far M. recutita blossoms has been used in treating skin inflammation, hemorrhoid, foot scars, urine burns in infants and in relieving pain and increasing the recovery rate of damaged tissues. 28,29 Lavandula officinalis The essence in Lavandula officinalis shoots contains flavonoid, tannin and coumarine. Its essence contains more than 40 compounds, the most important onesbeing linalool, linalyl acetate, cineol, nerol and borneol.…”
Section: Anethum Graveolensmentioning
confidence: 99%
“…Chamomilla contains flavonoids, which exert benzodiazepine-like activity (Avallone et al, 2000), and also has a phosphodiesterase inhibitory action, which leads to increased cAMP levels (Kuppusamy and Das, 1992). Gomaa et al (2003) reported the effect of flavonoids present in chamomilla on inhibition of morphine withdrawal in vitro. Recently, Kassi et al, (2004) demonstrated that aqueous extracts of chamomile induce osteoblast differentiation and have anti-cancer effects on breast cancer and uterine cancer cells in vitro (concentrations of 10-100 μg/mL).…”
Section: Chamomile (Matricaria Recutita)mentioning
confidence: 99%